High Temperature Interaction of NiO with Sodium Sulphate in SO2 Environment at 1100 and 1200 K - Hasan,S.K. (2011)
The present paper contains the results relative to the reaction of NiO with Na2SO4 in presence of SO2 (g) at 1100 and 1200 K. Nickel oxide (NiO) is produced by the oxidation of metal alloys in many industrial operations. The oxidation of metal and metal oxides in presence of molten salts and gas environment at high temperature is often called as hot corrosion. In this investigation the studies have been carried out taking into consideration the influence of SO2 partial pressure. The thermo-gravimetric studies have been carried out as a function of Na2SO4 concentration in the mixture. The reaction products identified by XRD analysis and surface morphologies of the products were discussed on the basis of metallographic and scanning electron microscopic (SEM) studies. The pH of the aqueous solutions of the reaction products were measured to observe the changes in the system with varying the Na2SO4 concentration. A quantitative estimation of soluble metal ions has also been carried out with the help of an atomic absorption spectrophotometer. The possibility of chemical reaction is established by thermodynamic calculations of free energies of the reaction products.